2020
DOI: 10.21203/rs.3.rs-118635/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age Impacts the Local Immune Response to Tuberculin Skin Challenge in Mycobacterium Bovis BCG-vaccinated Baboons

Abstract: Background - Individuals over the age of 65 are highly susceptible to infectious diseases, which account for one-third of deaths in this age group. Vaccines are a primary tool to combat infection, yet they are less effective in the elderly population. While many groups have aimed to address this problem by studying vaccine-induced peripheral blood responses in the elderly, work from our lab and others demonstrate that immune responses to vaccination and infectious challenge may differ between tissue sites and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Overall, chronic inflammation during aging hinders T-cell responses and interferes with vaccine efficacy [ 56 , 57 , 58 ]. For example, applying a delayed-type hypersensitivity model of Mycobacterium bovis BCG vaccination and tuberculin skin test in old baboons showed impaired immune responses to antigenic challenges that varied between tissue sites and the periphery, limiting appropriate immune memory responses [ 59 ]. A follow-up study demonstrated a decrease or delay in T cell recall responses to the pulmonary challenge site in aged BCG vaccinated rhesus macaques [ 60 ].…”
Section: Inflammaging And/or Immuno-senescence?mentioning
confidence: 99%
“…Overall, chronic inflammation during aging hinders T-cell responses and interferes with vaccine efficacy [ 56 , 57 , 58 ]. For example, applying a delayed-type hypersensitivity model of Mycobacterium bovis BCG vaccination and tuberculin skin test in old baboons showed impaired immune responses to antigenic challenges that varied between tissue sites and the periphery, limiting appropriate immune memory responses [ 59 ]. A follow-up study demonstrated a decrease or delay in T cell recall responses to the pulmonary challenge site in aged BCG vaccinated rhesus macaques [ 60 ].…”
Section: Inflammaging And/or Immuno-senescence?mentioning
confidence: 99%